The pastor in print : Genre, audience, and religious change in early modern England - Tan, Amy G. (Book collections on Project MUSE., 2022)
"The Pastor In Print explores the phenomenon of early modern pastors who chose to become print authors, addressing ways authorship could enhance, limit or change clerical ministry and ways pastor-authors conceived of their work in parish and print. It identifies strategies through which pastor-authors established authorial identities, targeted different sorts of audiences and strategically selected genre and content as intentional parts of their clerical vocation. The first study to provide a book-length analysis of the phenomenon of early modern pastors writing for print, it uses a case study of prolific pastor-author Richard Bernard to offer a new lens through which to view religious change in this pivotal period. By bringing together questions of print, genre, religio-politics and theology, the book will interest scholars and postgraduate students in history, literature and theological studies, and its readability will appeal to undergraduates and non-specialists."